Etika Etika ‘Tidak Enakan’ dalam Pencatatan Utang-Piutang: Sebuah Analisis Fenomenologis Sosial,Spiritual pada Komunitas Lokal - Sitti Mispa; Alimuddin Alimuddin; Syarifuddin Syarifuddin (Al-Buhuts, 2026)
Informal lending and borrowing practices are a social phenomenon that thrives within local communities and constitutes an important part of communities’ survival strategies. However, these practices are not merely viewed as economic transactions but as social relationships imbued with moral, cultural, and spiritual values. Nevertheless, most accounting literature continues to focus on economic and administrative aspects, leaving the social–spiritual dimensions of informal debt largely unexplored. This gap forms the basis for the urgency of this study. This research aims to uncover the subjective experiences of communities in interpreting debt-credit practices and to explain how the ethical norm of “feeling awkward” shapes the ways in which debts are given, recorded, and collected. A phenomenological approach was used to explore the depth of meaning and life experiences of those involved in debt within their social context. A total of 10 informants were involved, consisting of small shop owners, homemakers, and informal workers. Data were collected through in-depth interviews, participatory observation, and documentation of simple debt records, and then analyzed using Interpretative Phenomenological Analysis (IPA). The results indicate that debt is understood as a moral relationship rooted in empathy, solidarity, and a sense of responsibility. The ethic of “not wanting to cause discomfort” emerges as a social mechanism that regulates debt collection behavior with care in order to maintain harmony. Debt record-keeping is flexible, informal, and trust-based, while spiritual values such as trustworthiness, blessings, and the fear of disappointing others influence repayment priorities. This study contributes by expanding the understanding of social–spiritual accounting, demonstrating that accounting practices at the community level are shaped by morality, social relationships, and spiritual values embedded in local culture.